Diffusion kurtosis imaging and conventional diffusion weighted imaging to assess electrochemotherapy response in locally advanced pancreatic cancer - Granata Vincenza; Fusco Roberta; Setola Sergio Venanzio; Palaia Raffaele; Albino Vittorio; Piccirillo Mauro; Grimm Robert; Petrillo Antonella; Izzo Francesco (Radiology and Oncology, 2019)
The aim of the study was to evaluate diagnostic performance of functional parameters derived by conventional mono-exponential approach of diffusion weighted imaging (DWI) and by diffusion kurtosis imaging (DKI) in the assessment of pancreatic tumours treated with electrochemotherapy (ECT).